Numerical Simulation Research on Influencing Factors of Post-Fracturing Flowback of Shale Gas Wells in the Sichuan Basin - Wu, Jiangfa; Di, Yunting; Zhang, Jian; Li, Peiyun; Zhang, Deliang; Wang, Yan; Zhou, Hong (Frontiers in Earth Science, 2021)
The horizontal well multi-stage hydraulic fracturing technology is the most effective way to exploit shale gas resources. Compared with conventional reservoir fracturing, the flowback rate of fracturing fluid in shale reservoir is extremely low, and a large amount of fracturing fluid remains in the formation. Therefore, the research on the mechanism of shale reservoir fracturing fluid flowback process will contribute to laying a theoretical foundation for improving the effect of the innovation for increasing output of shale gas wells. Based on the shale in the Sichuan Basin, this paper firstly describes basic experiments on physical properties such as the porosity, permeability, mineral composition, wettability, and microstructure. The physical properties of shale reservoirs were also analyzed, which laid the foundation for subsequent modeling. Secondly, the CMG software is used to establish a numerical model that fits the characteristics of the flowback process. The effect of reservoir properties, fracturing parameters, drainage-production system, chemical permeability on gas and water production in the flowback process and their mechanisms are also analyzed. According to most of numerical simulation results, the lower cumulative gas production will be with the higher cumulative water production which means the higher flowback rate. The pursuit of only high flowback rate is not advisable, and the development of the drainage-production system requires reasonable control of the fracturing fluid flowback rate. This study provides a theoretical basis for the optimization of shale gas drainage-production system after hydraulic fracturing.